Virtual environments as a novel and promising approach in (neuro)diagnosis and (neuro)therapy: a perspective on the example of autism spectrum disorder - Ewa Sokołowska; Beata Sokołowska; Stanisław J. Chrapusta; Dorota Sulejczak (Frontiers in Neuroscience)
Over the last three decades, dynamically evolving research using novel technologies, including virtual environments (VEs), has presented promising solutions for neuroscience and neuropsychology. This article explores the known and potential benefits and drawbacks of employing modern technologies for diagnosing and treating developmental disorders, exemplified by autism spectrum disorder (ASD). ASD’s complex nature is ideal for illustrating the advantages and disadvantages of the digital world. While VEs’ possibilities remain under-explored, they offer enhanced diagnostics and treatment options for ASD, augmenting traditional approaches. Unlike real-world obstacles primarily rooted in social challenges and overwhelming environments, these novel technologies provide unique compensatory opportunities for ASD-related deficits. From our perspective in addition to other recent work, digital technologies should be adapted to suit the specific needs of individuals with ASD.